Proceso de búsqueda de clientes en el Mercado Internacional - Lladó Hernández, Miguel (2020)
The search for customers in different international markets has been - and is - controversial, due to the application of different methodologies andprocesses for market researchers. There is only one way to deal with this problem, and experiences of each researcher, the policies of the companies, the availability of resources and prior knowledge are factors that will affect the processes to apply.